Photophysics of O-band and transition metal color centers in monolithic silicon for quantum communications - Murat Can Sarihan; Jiahui Huang; Jin Ho Kang; Cody Fan; Wei Liu; Khalifa M. Azizur-Rahman; Baolai Liang; Chee Wei Wong (Communications Physics)
Abstract Color centers in the O-band (1260–1360 nm) are crucial for realizing long-coherence quantum network nodes in memory-assisted quantum communications. However, only a limited number of O-band color centers have been thoroughly explored in silicon hosts as spin-photon interfaces. This study explores and compares two promising O-band color centers in silicon for high-fidelity spin-photon interfaces: T and *Cu (transition metal) centers. During T center generation process, we observed the formation and dissolution of other color centers, including the copper-silver related centers with a doublet line around 1312 nm (* $${{{\rm{Cu}}}}_{n}^{0}$$ Cu n 0 ), near the optical fiber zero dispersion wavelength (around 1310 nm). We then investigated the photophysics of both T and *Cu centers, focusing on their emission spectra and spin properties. The * $${{{\rm{Cu}}}}_{0}^{0}$$ Cu 0 0 line under a 0.5 T magnetic field demonstrated a 25% broadening, potentially due to spin degeneracy, suggesting that this center can be a promising alternative to T centers.